ChemInform Abstract: Structure and Reactivity of Binary Au12Pt Cluster. Issue 4 (28th January 2014) - Kuang, Xiangjun; Wang, Xinqiang; Liu, Gaobin
Abstract An all‐electron scalar relativistic calculation on the geometrical structure and reactivity of Au12Pt cluster is performed by DFT with the generalized gradient approximation at PW91 level.